Impact of Taxpayer Compliance on Revenue Collection: A Case of Mbeya City, Tanzania - Beny Mwenda; Lewis Charles (International Journal of Management, Accounting and Economics)
The research aims to investigate the effect of taxpayer compliance on revenue collection using Mbeya City as a case study. Examine the degree of compliance, the variables influencing taxpayer compliance, and the relationship between taxpayer compliance and revenue collection. In the study, both qualitative and quantitative research methodologies were used. Data from 50 respondents were gathered via interviews and questionnaires. Multiple regression analysis, content analysis, and descriptive statistics were used to examine the data. The majority of respondents, according to the statistics, believe that taxpayers file returns on time, pay all taxes owed by the deadline, and accurately record their income. Furthermore, the majority of respondents said that tax rates, penalties and fines, tax audits, tax payer attitudes, and knowledge and education all have an impact on municipal taxpayer compliance. Furthermore, the data revealed a substantial link between taxpayer compliance and revenue collection. The study advised that authorities closely assess the impact of taxpayer compliance on tax collecting operations. Furthermore, it is proposed that the tax system give a clear and straightforward guidance on how to fill out tax returns, but also strengthen taxpayer education programs so that people understand their rights and duties as taxpayers.